Native aortic coarctation stenting in adults and adolescents: early and mid-term results of an adult interventional cardiology team - Akdemir, Ramazan; Gunduz, Huseyin; Murat, Sani; Kilic, Harun; Yeter, Ekrem; Tarik Agaç, Mustafa; Acar, Zeydin; Kaya, Yuksel; Dogan, Mehmet; Vatan, Mehmet; Cakar, Mehmet Akif; Erdem, Ali Fuat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: Stent implantation has evolved as an important therapeutic strategy for aortic coarctation. Aim : This study aimed to present the experience of aortic coarctation stenting using the Cheatham-Platinum stent by an Adult Interventional Cardiology Team. Material and methods: The data of 11 patients (ages were between 15 to 58 years) who underwent aortic coarctation stent implantation between 2008 and 2011 for moderate to severe native aortic coarctation were retrospectively collected. Results: Average systolic blood pressure was 175 ±35 mm Hg, and mean diastolic blood pressure was 115 ±15 mm Hg. Pressure gradient proximal and distal to aortic coarctation was 55.5 ±17.7 before the stenting. The invasive gradient decreased below 10 mm Hg in all patients. There were no complications except in one patient whose subclavian artery was occluded without any clinical finding. One patient had a totally occluded lesion, needing perforation for acquired interruption using a 0.35 inch hydrophilic wire under the supporting balloon. There was no aneurysm or restenosis at follow-up. Left ventricular functions completely recovered within 1 month in all patients. Conclusions : Stenting using the Cheatham-Platinum stent, either covered or bare, is safe in moderate to severe native aortic coarctation and provides an excellent transcoarctation gradient and clinical hypertension and left ventricular functional relief in adult patients.